Giant inguinal melanoma treated with complex oncological and reconstructive surgery: A case report. (August 2022) - Rastrelli, Marco; Di Prata, Claudia; Del Fiore, Paolo; Sbaraglia, Marta; Vindigni, Vincenzo; Bassetto, Franco
Abstract: A 53-year-old woman came to our attention with a giant inguinal mass that was growing in the last 5 months, so she underwent a total body CT-scan that showed a 25 × 16 × 21cm mass of the right inguinal region which was compressing the femoral vessels and infiltrated the omolateral rectum muscle, pulmonary embolism and thrombosis of the right femoral vein. We performed a tru-cut biopsy that was consistent with an undifferentiated round-cell sarcoma. So, we performed a wide excision of the mass and a reconstruction with a pedunculated muscular flap of the tensor muscle of the fasciae late, a graft of omologous fasciae late and a graft of the great saphena vein onto the superficial femoral artery. The histological examination of the specimen demonstrated instead an " atypical amelanotic sarcomatoid malignant melanoma " with rabdoid aspects. The patient underwent a radicalization surgery and reconstruction with microsurgical great dorsal and anterior serratus flap. To our knowledge, this is the biggest inguinal melanoma treated with surgical excision described so far. Highlights: Giant primary melanoma is generally accepted as greater than 10 cm, and almost associated with extensive metastatic disease. It is important the patients don't present with such a clinical challenge, the surgery could impact the quality of life. Patients with growing mass must be referred quickly to a diagnosis to obtain a less extent of surgical intervention.